ANALISIS INFLASI, CADANGAN DEVISA, DAN NERACA PEMBAYARAN TERHADAP PERUBAHAN KURS DAN PERTUMBUHAN EKONOMI PADA 10 NEGARA BERKEMBANG - Kurniawan, Sindu Bagas; Ratnawati, Tri; Rahmiyati, Nekky (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: In developing countries there are several ways to grow theireconomy, many factors influence. One of them is the inflation rate, foreignexchange reserves and balance of payments. In addition, the inflation rate,foreign exchange reserves and balance of payments can affect theexchange rate of a country's currency. So from that the researcher wants toknow how much influence the inflation rate, foreign exchange reserves andbalance of payments on currency exchange rates and economic growth indeveloping countries. This study will use a sample of 10 developingcountries in the Asian region, and this study will use quantitative descriptivemethods. This study will use secondary data which is then processed usingthe Partial Least Square (PLS) measurement model. The results of this studyare the inflation rate and balance of payments have a positive effect onchanges in the exchange rate of a country's currency, while the position offoreign exchange reserves has a negative effect. Then the inflation rate,foreign exchange reserves and balance of payments have a positive effecton a country's economic growth, while the exchange rate of a country'scurrency negatively affects a country's economic growth.Keyword : Inflation rate, Foreign Exchange, Balance of Payment, Exchangerate, Economic Growt